The Use of Qur'anic Verses in Local Traditions: Study of the Safar Bathing Tradition in Punggur Kecil Village, Kubu Raya Regency, West Kalimantan - Sahri (al-Afkar, Journal For Islamic Studies, 2023)
The aim of this article is to explain: First, the process, use, and meaning of Al-Qur'an verses in the Safar bathing tradition. Second, explaining the transmission of the Safar bathing tradition. The research locus is the Safar bathing tradition in Punggur Kecil Village, Kubu Raya district, West Kalimantan. Type of this research is a field study using the living Al-Qur'an model. The conclusion of this article is: First, the traditional implementation procession includes: 1) the time of implementation, carried out in the fourth week of the month of Safar, 2) the implementation process is after the Fajr prayer is finished, 3) the place of implementation of the Safar bath in each house and then praying together at mosque courtyard, 4) Making Safar water by religious leaders, and 5) The means and verses that are read, the means used adapt to the times and the verses that are read are known as the Salamun Seven verses, namely Qs. Yasin: 58, Qs. As-Saffat: 79, Qs. As-Saffat: 109, Qs. As-Shaffat: 120, Qs. As-Shaffat: 130, Qs. Az-Zumar: 73, Qs. Al-Qadr: 15 and the verses are termed the Salamun Seven verses. Second, related to the transmission of the Safar bathing tradition is the behavior of Ismail Mundu, a mufti of the Kubu kingdom, then this tradition has been preserved by the local community from generation to generation.